(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2023)
From the 1991 referendum on independence and the adoption of the Constitution up to date, Macedonian statehood has been going through several political transformations, of which, as key, we single out those of 2001, 2017 and 2018-19. All those turning points relate to the resolution of identity conflicts and disputes, both within the country and with neighbouring states. The purpose of this paper is to prove the hypothesis according to which the replacement of constitutionality as the foundation of the Macedonian state with contractual relations, which are later constitutionalized, leads to statehood erosion. In other words, instead of the Constitution representing a relatively permanent social contract of the citizens in the political community, the three contracts turned it into its opposite. Constitutional changes brought about through coercion and blackmail, that is, from a position of power, through international state building, have gradually created an increasingly weak and unsuccessful state, that is, a provisional state. Such an entity cannot hope to be incorporated into the European Union. More precisely, identity concessions accompanied by the dysfunctional state institutions result in effects contrary to the basic democratic imperatives and the principles contained in the Copenhagen criteria.